Medium-temperature high-activity brazing filler metal for brazing ceramic and metal and preparation method of medium-temperature high-activity brazing filler metal
By adding Sn, In, Ti-Zr low-melting intermediate alloys and a small amount of Si or Al elements to the solder, the problems of excessive brazing temperature and limited activity of the existing solder are solved, and medium-temperature and high-active brazing are achieved, which reduces the tensile stress on the side of the ceramic and improves the reliability of the brazed joint.
Patent Information
- Application Number
- CN202510092068.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
When brazing ceramics and metals, the brazing temperature is too high and the activity is limited, resulting in the ceramic side bearing a large tensile stress, which is prone to cause ceramic cracking.
By adding Sn, In, Ti-Zr low-melting intermediate alloys and a small amount of Si or Al elements, the brazing material is modified to reduce the brazing temperature and reduce the ceramic side tensile stress caused by the thermal expansion and contraction effect.
High-active brazing is achieved at medium temperature, reducing the residual stress of the brazed joint, improving the reliability of the brazed joint, and reducing the risk of ceramic cracking.
Smart Images

Figure CN119820176A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material engineering, in particular to a medium-temperature high-activity brazing filler metal for brazing ceramics and metals and a preparation method thereof. Background Art
[0002] Ceramic materials are resistant to high temperatures, have excellent heat dissipation and insulation properties, and are widely used in power facilities, electrical products, aerospace structural parts and functional parts. They have great demand and application prospects in arc-extinguishing switches / relays and new-generation semiconductor circuit board substrates. Realizing a reliable connection between ceramics and metals is the key to promoting the application of ceramic materials. For example, in vacuum arc-extinguishing chambers in aerospace devices and power transmission and transformation fields, it is necessary to achieve a reliable connection between the ceramic casing and the copper conductive component. For the connection of dissimilar materials, the brazing process has the advantages of being connectable, operable, similar in process, and high in bonding strength. The primary condition for achieving reliable brazing of ceramics and metals is good wetting of the brazing material on the ceramic. Most common metals have poor wettability on ceramics. Therefore, the current connection between ceramics and metals mostly uses pre-plated metals or active metal brazing methods.
[0003] At present, the most commonly used active metal brazing filler metal is AgCuTi based brazing filler metal, which has good wettability to ceramics and can be used to braze ceramics and copper. However, on the one hand, the activity of Ag-Cu-Ti based brazing filler metal is limited and requires high vacuum; on the other hand, the brazing temperature of Ag-Cu-Ti based brazing filler metal is relatively high, which can easily cause excessive thermal expansion and contraction after brazing, resulting in greater tensile stress on the ceramic side. Since the residual stress of the workpiece is positively correlated with the size / temperature, when the connection area is large or the temperature is high, the negative impact of excessive thermal expansion and contraction will be multiplied, and residual stress, deformation, and even cracking will occur in the joint between ceramics and metals.
[0004] Therefore, the defects of the current Ag-Cu-Ti solder, such as high brazing temperature and limited activity, seriously restrict the brazing size of the workpiece and the service reliability of the joint. It is necessary to optimize the design of the solder to reduce the residual stress of the brazed joint and improve the reliability of the brazed joint by lowering the solid-liquid phase line of the solder and increasing the activity of the solder. Summary of the invention
[0005] The present invention aims to provide a medium-temperature high-activity brazing filler metal for brazing ceramics and metals and a preparation process thereof. The brazing filler metal of the present invention is modified by adding specific elements to reduce the brazing temperature and reduce the excessive lateral tensile stress of the ceramics caused by the thermal expansion and contraction effect, thereby inducing the ceramic cracking.
[0006] The present invention adopts the following technical solutions to achieve the above-mentioned purpose:
[0007] A medium-temperature high-activity brazing filler metal for brazing ceramics and metals, comprising the following components in terms of mass percentage: 13-15wt% Sn, 3-6wt% In, 2-6wt% Ti-Zr low-melting master alloy, and a small amount of Si or Al elements mentioned below, and the remaining components are Ag-Cu eutectic;
[0008] Ti and Zr exist in the form of low-melting master alloys, and Ag and Cu exist in the form of eutectic.
[0009] As a preferred solution, 0.3-0.6wt% Si is also included to be suitable for brazing of Al2O3 ceramics.
[0010] As a preferred solution, Al 2-2.5wt% is also included to be suitable for brazing of AlN ceramics, wherein Al does not participate in smelting to form brazing alloy, but is directly added to the brazing seam in the form of foil or micro powder, and is pre-melted during the brazing process to guide wetting and improve the reliability of the brazing joint.
[0011] As a preferred solution, Al 1.5-2.0wt% is also included to be suitable for brazing of Si3N4 or SiC ceramics. Al does not participate in the melting of the brazing alloy, but is directly added to the brazing seam in the form of foil or micro powder, and is pre-melted during the brazing process to guide wetting and improve the reliability of the brazed joint.
[0012] As a preferred solution, Ni2-4wt% is also included to be suitable for brazing of ZrO2 ceramics. The introduction of Ni further improves the wettability of brazing to ZrO2 ceramics, thereby improving the connection reliability.
[0013] As a preferred solution, in the Ti-Zr low-melting master alloy, the Zr content is adjusted according to the Ti content to maintain the low-melting master alloy state, and the solder will undergo a solid phase transition below 700°C, which is beneficial to activate the ceramic surface.
[0014] As a preferred solution, the composition ratio of the Ti-Zr master alloy is between the eutectic point of the Ti-Zr binary phase diagram and the α-β minimum phase transition temperature point, and the atomic fraction of the Zr content is between 35% and 50%, that is, the mass fraction of the Zr content is between 50.65% and 65.30%, so that the solder has a lower solid-liquid phase line and activation temperature.
[0015] A method for preparing a medium-temperature high-activity brazing filler metal for brazing ceramics and metals, specifically comprising the following steps:
[0016] 1) Prepare raw materials: weigh the single metal or intermediate alloy according to the element mass percentage specified in the design document, store them separately after proportioning, and the metal purity requirement is not less than 99.95%. Among them, the Cu raw material is divided into two parts according to the following requirements.
[0017] 2) Ti metal blocks and Zr metal particles should be melted into a master alloy in an electric arc furnace with Cu equal to the sum of their weight. During melting, the metal blocks / particles are placed in the crucible of the electric arc furnace and the vacuum degree is pumped to 10 -2 Pa, then introduce Ar gas into the arc melting system until the pressure difference indicates -0.05MPa, and use the arc current specification of 300-400A to heat and melt copper, Ti and Zr;
[0018] 3) Repeated smelting: Repeat the melting 5-7 times until a homogenized CuTiZr master alloy cake is obtained;
[0019] 4) Slice cleaning: Use wire cutting to cut the intermediate alloy billet into thin slices with a thickness of 0.2 mm, and then use an organic solvent to clean the slices to remove impurities and oil stains on the surface.
[0020] 5) Prepare the raw materials separately and put them into a vacuum suspension melting furnace. When Ni or Si elements are present, Ni is added in the form of flakes and Si is added in the form of powder, and the raw materials are melted under the protection of Ar gas.
[0021] 6) Cast into slab and hot pickling to remove surface oxides and impurities.
[0022] 7) Hot rolling to form a thin strip with a thickness of 0.08-0.2 mm, cutting the burrs, hot pickling, washing with clean water, vacuum drying, and packaging for later use.
[0023] Compared with the prior art, the advantages of the present invention are: the use of Sn and In to synergistically reduce the solidus and liquidus of the solder is better than that of single Sn or In dominance, and the machinability is more effectively improved. At the same time, the amount of Sn added is controlled within the limit value that does not cause brittleness.
[0024] The active elements Ti and Zr are added in the form of low melting point master alloys, which makes the brazing temperature of the brazing filler metal lower and generates less brittle intermetallic compounds than the traditional Ag-Cu-Ti brazing filler metals, which mitigates the adverse effect of brittle intermetallic compounds on the impact toughness of the brazed joint; In and Si elements have a strong affinity for Al, so they are more suitable for brazing Al2O3 ceramics and metals. Al or Si elements have a strong affinity for Al2O3 or Si3N4 or SiC or AlN ceramics. In the brazing process of specific ceramics and metals, the introduction of Al or Si elements further improves the mechanical properties of the brazed joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM organizational structure diagram of the solder of Example 1 of the present invention.
[0026] Figure 2 This is the DTA curve diagram of Example 1 of the present invention.
[0027] Figure 3 This is the SEM organizational structure diagram of the solder of Example 2 of the present invention.
[0028] Figure 4 This is the DTA curve diagram of Example 2 of the present invention.
[0029] Figure 5 This is the SEM organizational structure diagram of the solder of Example 3 of the present invention. DETAILED DESCRIPTION
[0030] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0031] Embodiment 1:
[0032] A medium-temperature high-activity brazing filler metal for brazing ceramics and metals comprises the following components in mass percentage: 15wt% Sn, 5wt% In, 3wt% Ti-Zr low-melting master alloy (the mass fractions of Ti and Zr are 1.04wt% and 1.96wt% respectively), and 77wt% Ag-Cu eutectic (the mass fractions of Ag and Cu are 55.44wt% and 21.56wt% respectively).
[0033] In this embodiment, Figure 1 and Figure 2 From the SEM organizational structure diagram and DTA curve of the solder, it can be seen that the solder has no obvious defects and the solidus line of the solder is 675.68℃, which is nearly 105℃ lower than the most traditional inactive Ag-Cu eutectic solder.
[0034] Embodiment 2:
[0035] A medium-temperature high-activity brazing filler metal for brazing ceramics and metals comprises the following components in mass percentage: 14wt% Sn, 3.6wt% In, 3.4wt% Ti-Zr low-melting master alloy (the mass fractions of Ti and Zr are 1.6wt% and 1.8wt% respectively), and 79wt% Ag-Cu eutectic (the mass fractions of Ag and Cu are 56.88wt% and 22.12wt% respectively).
[0036] In this embodiment, Figure 3 and Figure 4 From the SEM organizational structure diagram and DTA curve of the solder, it can be seen that the solder has no obvious defects and the solidus line of the solder is 675.38℃, which is nearly 105℃ lower than the most traditional inactive Ag-Cu eutectic solder.
[0037] Embodiment 3:
[0038] A medium-temperature high-activity solder for brazing ceramics and metals comprises the following components in mass percentage: 14wt% Sn, 4wt% In, 3wt% Ti-Zr eutectic (the mass fractions of Ti and Zr are 1.04wt% and 1.96wt%, respectively), and 79wt% Ag-Cu eutectic (the mass fractions of Ag and Cu are 56.88wt% and 22.12wt%, respectively).
[0039] Embodiment 4:
[0040] A medium-temperature high-activity brazing filler metal for brazing Al2O3 ceramics and metals comprises the following components in percentage by mass: 15wt% Sn, 4wt% In, 0.3wt% Si, 5wt% Ti-Zr eutectic (the percentages of Ti and Zr are 2.4wt% and 2.6wt%, respectively), and 75.7wt% Ag-Cu eutectic (the mass fractions of Ag and Cu are 54.504wt% and 21.196wt%, respectively).
[0041] Embodiment 5:
[0042] A medium-temperature high-activity brazing filler metal for brazing ZrO2 ceramics and metals comprises the following components in percentage by mass: 14wt% Sn, 5wt% In, 3wt% Ni, 0.6wt% Si, 3wt% Ti-Zr low-melting master alloy (the percentages of Ti and Zr are 1.4wt% and 1.6wt% respectively), and 74.4wt% Ag-Cu eutectic (the mass fractions of Ag and Cu are 53.568wt% and 20.832wt% respectively).
[0043] In Examples 4 and 5, Si element or Ni element is added to make the brazing material more suitable for brazing special ceramics.
[0044] Embodiment 6:
[0045] A medium-temperature high-activity brazing filler metal for brazing Si3N4 or SiC ceramics with metals comprises the following components by mass percentage: 14wt% Sn, 5wt% In, 0.4wt% Si, 5wt% Ti-Zr low-melting master alloy (the percentages of Ti and Zr are 2.4wt% and 2.6wt% respectively), and 75.6wt% Ag-Cu eutectic (wherein the mass fractions of Ag and Cu are 54.432wt% and 21.168wt% respectively). When brazing Si3N4 or SiC ceramics, an aluminum foil of 2% of the mass of the brazing filler metal is pre-placed on the ceramic side to induce the brazing filler metal to wet the ceramic.
[0046] Embodiment 7:
[0047] A medium-temperature high-activity brazing filler metal for brazing ceramics and metals comprises the following components by mass percentage: Sn 13wt%, In 6wt%, Si 0.5wt%, Ti-Zr low-melting master alloy 3wt% (Ti and Zr percentages are 1.4wt% and 1.6wt%, respectively), Ag-Cu eutectic 77.5wt% (Ag and Cu mass fractions are 55.8wt% and 21.7wt%, respectively). When brazing AlN ceramics and Mo, 2.4% of the mass of the brazing filler metal is pre-placed in the form of micro-powder on the ceramic side with 200 mesh fine aluminum powder (directly added to the brazing seam).
[0048] In the present invention, the elements Sn and In are selected to synergistically reduce the solidus and liquidus of the solder, and the effect is better than that of a single element In. At the same time, the addition amounts of Sn and In do not exceed the embrittlement limit.
[0049] The active elements Ti and Zr are added in the form of eutectic, which makes the brazing temperature of the solder lower. Since Ti combines with Zr, the brittle Cu-Ti intermetallic compounds in the generated solder are less than those in the traditional AgCuTi solder, which reduces the damage of the brittle intermetallic compounds to the brazed joints (in the brazing interface reaction process, free Ti will correspondingly release Zr, and the presence of free dispersed particles helps to destroy the formation of continuous large-sized intermetallic compounds).
[0050] This solution contains In and Si elements, which have a strong affinity for Al. This brazing filler metal is particularly suitable for brazing Al2O3 ceramics and metals.
[0051] The invention is used for brazing connection between ceramics and metals, in particular, connection between Al2O3 ceramics and metals. For AlN, Si3N4 or SiC ceramics, aluminum foil or aluminum powder can be prefabricated during brazing.
[0052] Brazing of ceramics and metals is prone to cracking. There are two main reasons for this. First, most common metals have poor wettability to ceramics. Only a few active elements can produce good wettability to ceramics. Second, the thermal expansion coefficients of metals and ceramics are quite different. During cooling, the excessive differential thermal expansion and contraction cause the ceramic to bear a large tensile stress inside, thus causing the ceramic end to crack. There are two main theoretical and technical routes to solve this problem. One is to use an intermediate layer with a thermal expansion coefficient between the two to relieve stress, and the other is to use a low melting point brazing material to reduce the brazing temperature. The present invention is to modify the traditional Ag-Cu-Ti solder with a high brazing temperature by adding elements, using Sn as the main melting point lowering element, In as the secondary melting point lowering element and the active element, adding Ti and Zr, which often produce brittle phases, to form a low-melting intermediate alloy into the solder, and supplemented with Si to enhance the wettability of the solder to ceramics. That is, the present invention develops Ag-Cu-Sn-In-Si-Ti-Zr solder, thereby reducing the brazing temperature of the solder for brazing ceramics, thereby reducing the ceramic cracking caused by excessive thermal expansion and contraction caused by the excessively high brazing temperature.
[0053] The present invention and its embodiments are described above, and such description is not restrictive. The embodiments given in the examples and shown in the drawings are only one of the embodiments of the present invention, and the actual components are not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can creatively design component combinations and embodiments similar to the technical solution, which should all fall within the scope of protection of the present invention.
Claims
1. A medium-temperature high-activity brazing filler metal for brazing ceramics and metals, characterized in that: The composition includes the following components in terms of mass percentage: Sn 13-15wt%, In 3-6wt%, Ti-Zr low melting master alloy 2-6wt%, and the following respectively mentioned minor elements, and the remaining components are Ag-Cu eutectic; Ti and Zr are added in the form of low-melting master alloys, and Ag and Cu exist in the form of eutectic.
2. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: In order to avoid spontaneous combustion of Zr powder during smelting, the Zr element should be added in the form of Zr rods or Zr particles when smelting Ti-Zr master alloy.
3. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: It also includes Si0.3-0.6wt% to be suitable for brazing of Al2O3 ceramics.
4. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: It also includes Al2-2.5wt% to be suitable for brazing of AlN ceramics; Al does not participate in the melting of the brazing alloy, but is directly added to the brazing seam in the form of foil or micropowder.
5. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: It also contains Al1.5-2.0wt% to be suitable for brazing Si3N4 or SiC ceramics; Al does not participate in the melting of the brazing alloy, but is directly added to the brazing seam in the form of foil or micropowder.
6. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: Ni 2-4wt% is also included to be suitable for brazing of ZrO2 ceramics.
7. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: 0-5wt% Pd is also included to improve the strength and toughness of the solder.
8. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: In the Ti-Zr low-melting master alloy, the content of Zr is adjusted according to the content of Ti to maintain the state of the low-melting master alloy, and the solder will undergo a solid phase transition at a temperature below 700° C., which is beneficial to the activation of the ceramic surface; The composition ratio of the Ti-Zr master alloy is between the eutectic point of the Ti-Zr binary phase diagram and the α-β minimum phase transformation temperature point, and the atomic fraction of the Zr content is between 35% and 50%, that is, the mass fraction of the Zr content is between 50.65% and 65.30%, so that the solder has a lower solid-liquid phase line and activation temperature.
9. The medium-temperature high-activity brazing filler metal for brazing ceramics and metals according to claim 1, characterized in that: In the Ag-Cu eutectic, the content of Cu is adjusted according to the content of Ag to maintain the eutectic ratio, which is beneficial to the flow and spreading of the solder.
10. A method for preparing a medium-temperature high-activity brazing filler metal for brazing ceramics and metals, characterized in that: The specific steps include: 1) Prepare raw materials: According to the mass percentage ratio, the Cu raw material is divided into two parts according to the following requirements; 2) Ti and Zr and the same mass of Cu are pre-melted in an electric arc furnace to form a master alloy; the vacuum degree is pumped to 10 -2 Pa, then introduce Ar gas into the arc melting system until the pressure difference reading is -0.05MPa, and use the current specification of 300-400A to melt the raw materials; 3) Repeat smelting: repeat 5-7 times until a homogenized CuTiZr master alloy cake is obtained; Prepare the raw materials separately and put them into the vacuum melting furnace; 4) Slicing and grinding: Use wire cutting to cut the master alloy billet into thin slices with a thickness of 0.2 mm, and then use an organic solvent to clean the slices to remove impurities and oil stains on the surface; 5) All metals are placed in a suspension furnace. If Ni or Si is present, Ni is added in the form of flakes and Si is added in the form of powder; Melting under Ar gas protection; 6) Cast into slabs and use hot pickling to remove surface oxides and impurities; 7) Hot rolling to form a thin strip with a thickness of 0.08-0.2 mm, cutting the burrs, hot pickling, washing with clean water, vacuum drying, and packaging for later use.
Citation Information
Patent Citations
Active brazing method for improving performance of graphite / copper dissimilar material joint
CN113478040A
Brazing filler metal and preparation method and brazing method thereof
CN115178913A
Brazing material for joining ceramic-copper
JP1999130555A
Brazed structure of ceramic and metal
JP2006327888A
Ceramic circuit board and module using same
US20210176860A1